THE PREVALENCE OF APICAL PERIODONTITIS IN ARTERIAL HYPERTENSION AND NORMOTENSIVE PATIENTS USING CONE-BEAM COMPUTED TOMOGRAPHY. A COMPARATIVE ANALYSIS - Ioana Radu; Yllka Decolli; Bogdan Dobrovăț; Danisia Haba (Romanian Dental Association for Education, 2019)
Aim of the study The purpose of this study was to compare the prevalence and magnitude of periapical lesions in normotensive and hypertensive patients using cone-beam computed tomography (CBCT). Material and methods The aim of this study was to compare the aspects of periapical lesion in hypertensive and normotensive conditions using CBCT datasets for 132 patients. Periapical status of all included teeth was assessed by CBCT images. Statistical analysis was conducted using t-test, chi-square, and multiple regression. Results The prevalence of apical periodontitis was 16.95% in arterial hypertension and 15.63% in normotensive was significant difference. The mean of the average size of lesions between the two groups were almost comparable, 3.60 mm in arterial hypertension and 2.95 mm in normotensive patients. The number of arterial hypertension years before taking CBCT was not correlated with either the percentage nor the size of the lesions present. Conclusions Periapical lesion size did not differ between hypertensive and normotensive, there was no difference between this in terms of apical periodontitis.